Sportkardiologie - Postler T; Schulz T; Oberhoffer R (Dynamic Media Sales Verlag, 2017)
Background: To counteract cardiovascular risk factors in childhood, the German Heart Foundation developed Skipping Hearts for schools: Aim of this rope skipping project is to promote physical activity by providing pleasure in exercise, which, in turn would improve physical performance. The current evaluation study investigated the effectiveness of this preventive measure. Methods: Using a pre-post-design, anthropometric characteristics, health parameters and motor skills of 1,493 elementary school children (9.030.65 years) were tested. 1,161 children received a one-stage (SHBasic: n=721) or two-stage training (SHChampion: n=440), 332 children served as controls. To score the project, all children and the coordinating teachers of the examined schools (n=24) were surveyed by means of questionnaires. Additionally, physical activity was measured by accelerometry (sub-sample: n=89).Results: Endurance, strength, coordination and shoulder mobility showed improvements in the students participating in Skipping Hearts compared to the control group (p<0.001). Also, an increased activity level (p=0.027) and a lower rise in body fat (p<0.001) were ascertained after the project. Children in SHChampion showed greater developmental leaps and changes towards health attitude/behavior than the SHBasic.Discussion: Skipping Hearts elicited great enthusiasm among the children and received high acceptance/satisfaction ratings from the teachers. Positive effects were observed on motor skills, body composition and exercise behavior in the 5-month study period. Thus the measure is successful in the short term. Further conclusions about sustainable improvements in health are not yet possible. KEY WORDS: Health Promotion, Physical Activity, Children, Elementary School, Rope Skipping